Ground-based validation of the MetopA and B GOME-2 OClO measurements - Pinardi, G.; Roozendael, M.; Hendrick, F.; Richter, A.; Valks, P.; Alwarda, R.; Bognar, K.; Frieß, U.; Granville, J.; Gu, M.; Johnston, P.; Prados-Roman, C.; et al. (2021)
This paper reports on ground-based validation of the atmospheric OClO data record produced in the framework of EUMETSAT’s Satellite Application Facility on Atmospheric Chemistry Monitoring (AC SAF) using the GOME2-A and -B instruments over the 2007–2016 and 2013–2016 periods, respectively. OClO slant column densities are compared to correlative measurements collected from 9 NDACC Zenith-Scattered-Light DOAS (ZSL-DOAS) instruments distributed in both the Arctic and Antarctic. Sensitivity tests are performed on the ground-based data to estimate the impact of the different OClO DOAS analysis settings. On this basis, we infer systematic uncertainties of about 25 % between the different ground-based data analysis, reaching total uncertainties ranging from about 26 % to 33 % for the different stations. Time-series at the different sites show good agreement between satellite and ground-based data, both for the inter-annual variability and the overall OClO seasonal behavior. GOME-2A results are found to be nosier than those of GOME-2B, especially after 2011, probably due to instrumental degradation effects. Daily linear regression analysis for OClO activated periods yield correlation coefficients of 0.8 for GOME-2A and 0.87 for GOME-2B, with slopes of 0.64 and 0.72, respectively. Biases are within 8 x 1013 molec/cm2 with some differences between GOME-2A and GOME-2B, depending on the station. Overall, considering all the stations, a median bias of about −2.2 x 1013 molec/cm2 is found for both GOME-2 instruments.